Analysis of Factors Affecting Outpatient Loyalty at Ananda Bekasi Hospital with Satisfaction as an Intervening Variable - Nugroho, Fathoni; John EH J. FoEh; Sugeng Suroso (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to examine the factors that influence outpatient loyalty at Ananda Bekasi Hospital with satisfaction as an intervening variable. The method used in this study is a quantitative method using a causal research survey approach. This research was conducted at Ananda Bekasi Hospital with a total sample of 257 outpatients from an average patient population per month of 5,000 people served by outpatient services. The data analysis technique in this study used the Structural Equation Modeling - Partial Least Square (SEM-PLS) method with the help of the SMART PLS 4.0 Application and the SPSS Version 25 Application to carry out research data analysis. In this study, instrument testing was carried out by conducting validity tests, reliability tests, outer models, inner models and hypothesis testing.